Diverse impacts of sea ice and ice shelf melting on phytoplankton communities in the Cosmonaut Sea, East Antarctica - Qianqian Qi; Qiang Hao; Guang Yang; Shunan Cao; Jiawen Kang; Jiashun Hu; Minfang Zheng; Mengya Chen; Jianfeng He; Min Chen (Environmental Research Letters)
Antarctic sea ice and glacier melt profoundly impacts marine ecosystems. Our study in the Cosmonaut Sea summer measures seawater oxygen isotopes, size-fractionated chlorophyll-a, and phytoplankton communities. We quantify sea ice meltwater, meteoric water, and winter water contents using a Bayesian isotope-mixing model. Contrary to common belief, our findings suggest that the reduced net export of sea ice to the north and the basal melting of ice shelves have deepened the mixed layer in coastal waters, altering the survival depth of phytoplankton. Freshwater primarily stimulates phytoplankton growth by supplying dissolved iron rather than by increasing water stability, which influences the size distribution and species composition of the phytoplankton community. These insights highlight the complex interplay between freshwater inputs, nutrient dynamics, and phytoplankton communities, and are crucial for understanding the dynamics of Antarctic ecosystem and its vulnerability to climate change.